ANALISIS PENILAIAN ORGANOLEPTIK CAKE BROWNIES SUBTITUSI TEPUNG Wikau Maombo - Noviyanti, Noviyanti (Jurnal Sains dan Teknologi Pangan, 2016)
Generally brownies cake is baked with flour ingredient. The experiment of baking brownies with  wikau maombo flour and plain flour is the attempt to diversify food for gainning benefit of local food commodity as the relative economic price ingredient and it can reduce the use of wheat flour with high gluten. Excessive consumption of gluten will cause negative effects. Brownies cake product baked with substituted flour and wikau maombo flour was analyzed by organoleptic as a method to determine the quality of product from wikau maombo flour. This study employed Completely Randomized Design with factorial. The first factor was cassava B which consisted of two levels, the sweet variety (B1), and bitter variety (B2). The second factor was the concentrate of flour increasement which consisted of five levels, namely 0%  flour increasement (T0), 10% flour increasement (T1), 15% flour increasement (T2), 25% flour increasement (T3), 100% flour increasement (B4). Those factors were combined and obtained 10 treatments. Each treatment combination underwent 3 repetitions so it reached 30 units of experiment in total. The result of oleptic organ testing indicated panelis assessment of colors 3.64 (favorited), 3.89 aroma (favorited), 3.69 texture (favorited), and 3.93% taste (favorited). Keywords : Brownies cake, wikau maombo flour, wheat flour.